Examining the Importance of Religious Commitment Towards Takaful Participation Intention (TP1) - Hartini, Ab Ghani; Salman, Lambak; Sofiah, A.B.; Mustafa, Dakian (2016)
Malaysia is one of the Muslim countries committed in developing a complete Islamic financial system including Islamic insurance (Takaful). Until today, Takaful penetration rate lags behind conventional insurance. This dismal performance, despite government’s commitment and the growing inclination towards ‘Islamisation’, warrants an empirical investigation. A sample of 500 respondents classified as professional was taken to examine the effect of religious commitment on Takaful participation intention, using Theory of Planned behaviour as the theoretical foundation. This chapter found that religious commitment is positively related to the Takaful participation intention (TPI). Not only that, religious commitment has the greatest influence on TPI.